The Economic Impact of Biosimilars on Chronic Immune-Mediated Inflammatory Diseases - Pentek, Marta; Zrubka, Zsombor; Gulacsi, Laszlo (Current Pharmaceutical Design, 2017)
Background: Biological drugs represent highly effective but costly treatments for chronic immunemediated inflammatory diseases posing substantial burden on health care budgets. Introduction of biosimilars since 2013 has brought forward the potential of market competition, and as a societal benefit, the hope of increased access at a lower cost. Objective: We aim to provide a descriptive review on economic aspects and market changes related to the introduction of biosimilar drugs. Method: Our focus is on chronic immune-mediated inflammatory conditions in rheumatology, gastroenterology and dermatology. Based on available literature data, we discuss the determinants of access to biological treatment, summarize the available health economic evidences with special focus on cost-utility and budget impact analyses. Market penetration of biosimilars and their overall impact on biological markets are analyzed. Results: Biosimilar markets are country specific due to differences in the regulatory and reimbursement systems. Cost-utility analyses suggest, that given the lower price of biosimilars, formerly established biological treatment sequence practices and the eligibility criteria for biological treatment deserve reconsideration. Budget impact analyses forecasted significant budget savings in various diagnoses and countries, providing opportunity for the treatment of more patients. Conclusion: Biosimilars may contribute to better patient-access and provide savings to governments. To increase their acceptability, further clinical evidences and real world experiences are needed, as well as education of physicians and patients. The high biosimilar penetration rates in Norway, Denmark and Poland suggest that policies which support interchanging from the reference product may be important drivers of biosimilar uptake.
Keywords: access